Advanced Analytical Methods for Phenolics in Fruits - Kafkas, Nesibe Ebru; Kosar, Muberra; Oz, Ayse Tulin; Mitchell, Alyson E. (Wiley-Hindawi, 2018)
Phenolic compounds are a group of secondary plant metabolites, many with health-promoting properties that are present in all parts of plants. They have an aromatic structure, including either one or more hydroxyl groups giving them the ability to stabilize free radicals and protect biological tissues against damage related to reactive oxygen species. Phenolic compounds are concentrated in the fruit of plants, and therefore, the fruit can be an important dietary source of these phytochemicals, which exist as monomers, or bound to one another. Polyphenolic compounds are classified into different subclasses based upon the number of phenol ring systems that they contain, saturation, and length of the carbon chain that bind the rings to one another. The phenolic acids present in fruit tissues protect the plant against disease, infections, UV radiation, and insect damage. For this reason, the beneficiary effects of phenolic compounds are continually being investigated for their health-promoting properties and for meeting increased consumer demand for healthy nutritious food. Due to the functional properties of polyphenolic compounds, there is increased interest on improving extraction, separation, and quantification techniques of these valuable bioactive compounds, so they can be used as value-added ingredients in foods, pharmaceuticals, and cosmetics., is review provides information on the most advanced methods available for the analysis of phenolics in fruits.
Keywords: Performance Liquid-Chromatography; Pulsed Electric-Fields; Antioxidant Activity; Acids; Anthocyanins; Plants; Copigmentation; Extraction; Flavonoids; Capacity